The Relationship between Exposure to Hand-Arm Vibration (HAV) and Work Fatigue in Tailors in Makassar - Amalia, Alfiyyah; Ramadhani, Fadilah; Hafiza Ansar, Fahriyana; Nuriski, Muh Asril; Widiastuty, Lilis; Ekasari, Ranti (Unihealth Community Research, 2026)
Encountering mechanical vibration represents a notable physical occupational risk that can lead to work-related health issues, including occupational fatigue, especially in jobs that require the repetitive operation of vibrating equipment, such as tailoring in the informal sector. This research sought to investigate the correlation between hand-arm vibration (HAV) exposure and work-related fatigue among informal-sector tailors in Makassar City. A quantitative, cross-sectional methodology was utilized, incorporating 30 participants chosen via simple random selection. Vibration exposure was quantified in m/s² using the ISO 5349-1:2001 standard, whereas occupational tiredness was evaluated via the tiredness Feeling Measurement Tool Questionnaire (KAUPK2). Bivariate data examination was performed via Fisher's Exact test. A significant portion of participants experienced minimal vibration exposure and indicated modest degrees of work-related weariness. Statistical examination indicated no significant correlation between hand-arm vibration exposure and work-related weariness (p>0.05). The results indicate that minimal vibration exposure might not be adequate to substantially provoke occupational tiredness in the studied group. The lack of a statistically significant correlation suggests that alternative factors might have a more considerable influence on the emergence of work-related weariness among tailors, especially considering the minimal vibration exposure noted in this environment. Additional investigation utilizing a longitudinal framework and an expanded sample population is advised to thoroughly assess the impact of vibration exposure and ergonomic elements on work-related weariness.